Estimation of critical dry spell analysis in Shipra basin, Madhya Pradesh - JAISWAL, SMITA; CHANDOLA, V. K.; GALKATE, RAVI; SINGH, PRASHANT (Journal of Soil and Water Conservation, 2020)
Rainfall has a major role in rainfed agriculture. So, estimation of critical dry spells along with actual evapotranspiration assist in the design of irrigation systems under irrigated and rainfed agriculture. In this context, a study was undertaken to estimate the critical dry spell (CDS) in Shipra Basin, (Madhya Pradesh, India) using the rainfall data of 24 years. The daily rainfall and evaporation data of the Shipra basin was obtained from the National Institute of Hydrology (NIH), Regional Centre, Bhopal. The Simulation of Reference evapotranspiration (ET0) was performed using the Penman-Monteith method in CROPWAT 8.0 software. The data was analyzed to determine the mean dates of Onset of effective monsoon (OEM), end monsoon with standard deviation. The result showed the Dry spells were found during every year and the mean dates of Onset of effective monsoon(OEM) were found to be from 15thJune to 20th June. The mean date of end of monsoon was found to be 17th to 21thSeptember, the standard deviation of onset of monsoon value ranges between 7th to 16th. The mean dates of critical dry spells were 24th June to 1st July with mean duration of 13 to 32 days for the first CDS, 30th July to 16th September with mean duration of 11 to 37 days for the second CDS, 16th August to 5th September with mean duration of 10 to 40 days for the third CDS and 17th August to 20thSeptember with mean duration of 11 to 32 days for the fourth CDS.